FIGURATIVE SYMBOLS RELATED TO THE IMAGE OF NATURE IN LYRICS - Rustamova Shakhnoza Abdurakhimovna (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract: This article investigates the figurative symbols associated with the depiction of nature in lyrics. Through a comprehensive analysis of literature and qualitative research methods, it examines how songwriters utilize metaphor, imagery, and symbolism to portray the natural world. The study explores the diverse representations of nature in lyrics and their underlying meanings, shedding light on the symbolic significance of elements such as animals, landscapes, and weather patterns. By delving into the interplay between language and imagery, this research elucidates the evocative power of nature-related symbols in songwriting.